Development of a mobile 3d mapping system in the Republic of Kazakhstan - Dzhurinskaya, Татьяна; Kurmankina, Дария (Рroblems of engineering and professional education, 2023)
Modern technologies and their relevance are considered in this work. The improvement of Torsop's production output will create an opportunity for effective and emergence, and will play an important role in geodetic works.